(untitled) (GEOmedia, 2016)
Organizations managing underground networks are asking, with growing strength, upgraded information systems and we can find several software/ hardware houses offering solutions for mapping these underground networks in order to visualize them. In this paper we try to show the 3D/4D GIS solutions by Skyline for underground networks’ visualization and querying: one simply procedure for the visualization and a slightly complex one for alphanumeric data querying.